Determinants of Tax Audit Effectiveness in Southwestern Nigeria - Salawu, Mary Kehinde; Adedeji, Zacch Adelabu; Iwamitigha, Ayodeji Moses; Olanisebe, Moses Babatunde (International Review of Management and Marketing, 2026)
The study assessed the determinants of effectiveness of tax audits in southwest Nigeria. The study was based on descriptive survey research design using questionnaire administered to targeted population. The study population consists of the four hundred (400) staff members of Nigeria Revenue Service (NRS) in Southwestern Nigeria as at 2026. Based on purposive sampling technique, 364 staff members involved in audit and collection functions were selected as the sample size (tax controllers, auditors, and other relevant officers). A quantitative method of analysis was employed through an adapted questionnaire which was distributed to 364 staff members, asking about their thoughts on tax audit effectiveness. Descriptive statistics and Feasible Generalized Least Squares (FGLS) were used to examine the determinants of effectiveness of tax audits practice. Results from analysis showed that audit quality and professionalism, legal framework and tax laws, and audit procedure and methodology have significant impact on tax audit effectiveness. On the other hands, determinants such as risk management and prioritization, taxpayers’ cooperation and compliance culture, audit follow-up and enforcement, and political support and stakeholders’ engagement have insignificant impact on tax audit effectiveness in southwest Nigeria. The study concluded that there is significant variation in the determinant factors influencing tax audit effectiveness in southwest Nigeria. Among other things, the study recommends that government should strengthen the institutional, legal, and procedural factors thorough tax policy as they are essential for enhancing the effectiveness of the tax audit system in Southwestern Nigeria.